Kajian budaya organisasi dengan kepuasan kerja di kalangan pekerja sokongan Jabatan Pertanian Sarawak (Ibu Pejabat), Kuching - Lee, Amelia Sze Chui. (Universiti Malaysia Sarawak, (UNIMAS), 2001)
This study aims to determine the relationship between organization culture and job satisfaction among support staffs at Jabatan Pertanian Sarawak (Headquarters), Kuching. Factors that are included in this study are gender, age, length of service, leadership, communication, working environment, compensation omJ benefits system. Selected concepts from previous studies are revealed to further enhance the IUlderstanding ofreaders. In this study. the questionnaire technique is used to obtain feedback and relevant data. A total of 62 support staffs were randomly chosen as the sample of this study. The respondents' background, the respondents' opinion towards the related organization culture factors and opinions of related job satis/action factors were examined. The data of this study was analysed using the descriptive and inferential statistics. Majority of the respo1!lhTll.f (77.4 percent) have a moderate job satisfaction level. The T test, Pearson Correlation test, One·Way ANOVA test and Multiple Linear Regression test were used to test the hypotheses. The results show there is na significant difference ofjob satisfaction between the gender, age and length of service. The correlation between leadership, communication, working environment, compensation and benefits system with the job satisfaction are found to be positive and significant. In terms of compensation and benefits system, it shows a moderate correlation with job satisfaction. In terms of leadership, communication, working environment, the correlation is found to be weak. It is found that the compensation and benefits system is the dominant factor, followed by working environment that cont